2020
DOI: 10.1080/10549811.2020.1841008
|View full text |Cite
|
Sign up to set email alerts
|

“Maxed Out on Efficiency”: Logger Perceptions of Financial Challenges Facing Timber Operations

Abstract: Loggers play critical roles in forest management and resource production, yet supply chain pressures can challenge their economic sustainability. We examine logger perspectives on efficiency, financial challenges, and potential solutions from two contrasting perspectives: 1) business strategy and 2) treadmill of production, a sociological critique of resource production that links economic and ecological sustainability. To provide in-depth perspectives based on lived experiences, we conducted interviews with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Indeed, studies have found that the average log truck involved in a crash is five or more years older than other heavy trucks [12,44]. Third, some companies continue operating when they are losing money as long as their cash flows are positive [29][30][31]. These companies are said to be "running on equity".…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, studies have found that the average log truck involved in a crash is five or more years older than other heavy trucks [12,44]. Third, some companies continue operating when they are losing money as long as their cash flows are positive [29][30][31]. These companies are said to be "running on equity".…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, timber transportation may serve as a "loss leader" for an otherwise profitable logging or timber purchasing business [11]. In other cases, companies may operate unprofitable businesses when cash flow is positive, even though the company is losing money because of unrecovered depreciation [29][30][31]. These businesses are said to be "running on equity".…”
Section: Introductionmentioning
confidence: 99%
“…Logging businesses in the southern US have historically favored the adoption of new technology and machinery to maintain or enhance production levels in the face of labor shortages [48]. However, the cost of the specialized machinery that allows for operating at the same production efficiency with lower employment in logging crews continues to increase due to various factors including global supply chain issues [16].…”
Section: Business Challengesmentioning
confidence: 99%
“…Mill issues including low prices and payments, outages and slowdowns, low or strict quotas, procurement problems, and preferential treatment of some logging companies were frequently cited as challenges. Mill quotas, in particular, are a historic complaint for logging businesses throughout the US [7,10,16,18] and have been for many years. These quotas present a market-based cause for underutilized production capacity for logging business crews, indicating that there is an oversupply of available timber within the area.…”
Section: Business Challengesmentioning
confidence: 99%
See 1 more Smart Citation